Macular Changes in a Mucopolysaccharidosis Type I Patient with Earlier Systemic Therapies - Augusto Magalhães; Ana Maria Cunha; Rodrigo Vilares-Morgado; Elisa Leão-Teles; Esmeralda Rodrigues; Manuel Falcão; Ângela Carneiro; Jorge Breda; Fernando Falcão-Reis (Case Reports in Ophthalmological Medicine)
Purpose. To describe retinal findings in a patient with mucopolysaccharidosis type I (MPS I) that underwent an early treatment with hematopoietic stem cell transplantation (HSCT) and enzyme replacement therapy (ERT). Case Report. We describe a case of a 12-year-old female with a biochemical and genetic diagnosis of MPS I. She underwent HSCT and ERT on the first year of life. The visual acuity was 5/10 in both eyes and she had bilateral grade 2 corneal haze. Spectral domain optical coherence tomography (SD-OCT) revealed thickening of the external limiting membrane (ELM) at the fovea. In the parafoveal and perifoveal regions, SD-OCT displayed a loss of the interdigitation, ellipsoid, and myoid zones and of the ELM accompanied by progressive thinning of the outer nuclear layer. Fundus infrared imaging revealed a hyperreflective ring centred on the fovea and hyporeflective areas in temporal parafoveal regions in both eyes. En face OCT imaging revealed two hyperreflective rings on the outer retinal level. Conclusion. This patient developed macular changes with foveal deposition of hyperreflective material and parafoveal thinning, despite early systemic treatment. Systemic therapies can provide an increase in life expectancy and stabilize visual acuity and corneal clouding, although their effect on retinal degeneration is unknown.